Chikungunya virus infection in human microglial C20 cells induces mitochondria-mediated apoptosis - Kumar, Narendra; Santhoshkumar, Rashmi; Venkataswamy, Manjunatha M. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Chikungunya virus (CHIKV) infection is associated with acute clinical manifestations and chronic joint inflammation. CHIKV has emerged as a significant causative agent of central nervous system (CNS) complications, including encephalitis and related sequelae. Microglial cells, crucial for immune responses and tissue repair in the CNS, play a vital role in the host response to viral infections, with their activation potentially leading to either protection or pathology. In this study, the infection biology of CHIKV in the C20 human microglial cell line was investigated. Methods The permissiveness of C20 cells to CHIKV infection was assessed, and viral replication kinetics were compared to Vero E6 cells. Cytopathic effects of CHIKV infection on C20 cells were examined, along with ultrastructural changes using transmission electron microscopy. Additionally, apoptosis induction, mitochondrial membrane potential, and alterations in cell surface marker expression were evaluated by flow cytometry. Results CHIKV infection demonstrated permissiveness in C20 cells, similar to Vero cells, resulting in robust viral replication and cytopathic effects. Ultrastructural analysis revealed viral replication, mature virion formation, and distinctive cytoplasmic and nuclear changes in infected C20 cells. CHIKV infection induced significant apoptosis in C20 cells, accompanied by mitochondrial membrane depolarization and altered expression of cell surface markers such as CD11c, CD14, and HLA-DR. Notably, decreased CD14 expression was observed in CHIKV-infected C20 cells. Discussion The study findings suggest that CHIKV infection induces apoptosis in C20 microglial cells via the mitochondrial pathway, with significant alterations in cell surface marker expression, particularly CD14 that is linked with apoptosis induction. These observations provide valuable insights into the role of human microglial cells in the host response to CHIKV infection and contribute to the knowledge on the neuropathogenesis of this virus.